Diverse Knowledge in the Transcomplex Reality of Human Activity. - González Labrada, Guillermo Calixto (Conexiones UG, 2025)
The contrast between the multidimensional universal scenario is contradictory with a process of knowledge of mobilizing tendency in classical rationalism, which does not always consider the mediations of plural and heterogeneous interinfluences of the diversity of knowledge. The objective: to complement previous conceptualizations with the polyrelational diverse transdisciplinary holistic hologrammatic ecoepistemy for any of the processes of human activity. Methodology: a preferential logic for the inexactness and unknown of knowledge, directed by the transmethod of diverse eco-combination of dialogical dynamics of creative prospective problematization. The result: a diverse polyrelational eco-epistemic matrix methodology, a guarantee of sustainability in the subjects’ intentionality, from their multiple self-management capacity with sociocognitive precedence to unknown multidirectional transrelations; debunking myths; configure systems of confluences and transrelations of multidimensional-polyrelational network systems that typify a transcomplex reality. The option reaffirms the potential of diversity as an inherent quality of the human condition with the admission of plural interinfluences in a scenario with ethics, aesthetics, and harmony with the environment. The existence of problematizing situations where the environment, emerging ecosystems, culture, the interconnections between them, or from one of them, converge, is a suggestive pretext for emerging this reality, and embracing the unknown.